GENDER AND RACIAL IDENTITY, NORMATIVE PERCEPTIONS OF PHYSICAL ACTIVITY, AND PHYSICAL ACTIVITY AMONG COLLEGE-AGED AFRICAN AMERICAN WOMEN - Thornton, Shelly A (East Carolina University, 2021)
African American women have a compounded risk for chronic disease development, poorer disease-related quality of life, and chronic disease mortality. While regular engagement in physical activity can reduce these risks, African American women are significantly less likely to engage in physical activity when compared to their gender and racial counterparts. Therefore, it is important to identify factors that may contribute to physical activity and protect against physical inactivity among African American women. Social Identity Theory may offer a framework for understanding gender and racial influences on exercise behaviors. Social Identity Theory posits that individuals strengthen their sense of belonging with social groups by adopting normative perceptions, attitudes, values, and behaviors. Prior research has established associations between gender and racial identity and exercise behaviors as well as associations between normative perceptions of physical activity and exercise behavior. Inferences from prior research suggests there is a link between gender and racial identity and normative perceptions of exercise behavior, however this link has not been established. Female gender seems to be a risk factor for physical inactivity across the developmental continuum, however research examining African American cultural influences on physical activity has yielded mixed findings. This dissertation sought to examine gender and racial influences on exercise behavior in a sample of African American college-aged women guided by the Social Identity theoretical framework. More specifically, this study sought to (1) comprehensively measure gender and racial identity domains and compare strengths of identity across these two domains, (2) examine perceived physical activity norms for gender and race, (3) determine whether gender and racial identity predict physical activity, (4) determine whether gender and race-related physical activity norms predict physical activity, and (5) examine links between gender identity and gender-related physical activity norms and links between racial identity and race-related physical activity norms. A total of 188 African American undergraduate women completed an online survey that assessed multiple dimensions of gender and racial identity, normative perceptions of physical activity for gender and race, and exercise behaviors. On average, participants reported strong emotional and psychological connection to other women and African Americans. They also reported strong, positive feelings towards being women and African American. Lastly, participants reported that physical activity was normative for their female friends, African American friends, and normative for broader reference groups of women in general and African Americans in general. Overall, physical activity was perceived by participants to be more normative for African Americans than for women and more normative for broader reference groups of women and African Americans as compared to female and African American friend groups. In terms of predicting physical activity, the full model of Social Identity Theory was not supported for either gender or racial influences; however, results indicated that both positive African American racial identity and perceiving physical activity as normative for one's African Americans friends were positive influences on exercise behaviors. Compared to racial identity, gender identity did not predict physical activity, but positive female gender identity was linked to perceiving exercise as more normative for one's female friends, establishing what appears to be the first empirical link between identity and norms in the social identity theory literature. Clinical implications of these findings and future directions for research are discussed, particularly as it relates to increasing and sustaining motivation for exercise among African American Women.
Keywords: multidimensional identity measurement; physical activity; health promotion; African American women--Health and hygiene; African American college students--Health and hygiene; African American women--Race identity; Exercise--Psychological aspects; Gender identity